2020
DOI: 10.3390/ijerph17207481
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual–Cognitive Function and Unplanned Athletic Movement Task Performance: A Systematic Review

Abstract: The performance of choice-reaction tasks during athletic movement has been demonstrated to evoke unfavorable biomechanics in the lower limb. However, the mechanism of this observation is unknown. We conducted a systematic review examining the association between (1) the biomechanical and functional safety of unplanned sports-related movements (e.g., jumps/runs with a spontaneously indicated landing leg/cutting direction) and (2) markers of perceptual–cognitive function (PCF). A literature search in three datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… a Data analyzed by Wilke et al 65 BH, ball handling; CCR, co-contraction ratio; CRI, concussion resolution index; HAM, hamstring; HP, high performance; IC, initial contact; ImPACT, immediate postconcussion assessment and cognitive testing; LP, low performance; pGRF, peak ground-reaction force; pKAbA, knee abduction angle; pKAbM, knee abduction moment; pKFA, knee flexion angle; SDMT, symbol digit modalities test; sEMG, surface electromyography; STOP-IT, stop signal task; TMT-A/B, trail-making-test A/B; TTS bw, time to stabilization, using the participant’s body weight; TTS fn, time to stabilization, using the normal force; QUAD, quadriceps. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Data analyzed by Wilke et al 65 BH, ball handling; CCR, co-contraction ratio; CRI, concussion resolution index; HAM, hamstring; HP, high performance; IC, initial contact; ImPACT, immediate postconcussion assessment and cognitive testing; LP, low performance; pGRF, peak ground-reaction force; pKAbA, knee abduction angle; pKAbM, knee abduction moment; pKFA, knee flexion angle; SDMT, symbol digit modalities test; sEMG, surface electromyography; STOP-IT, stop signal task; TMT-A/B, trail-making-test A/B; TTS bw, time to stabilization, using the participant’s body weight; TTS fn, time to stabilization, using the normal force; QUAD, quadriceps. …”
Section: Resultsmentioning
confidence: 99%
“…Giesche et al 27 explored the relationship of neurocognitive performance with biomechanical stability and unplanned landing cost. The results obtained by Niederer et al 50 were reanalyzed by Wilke et al 65 to investigate the relationship between landing success/errors and cognitive performance. Finally, Fischer et al 24 studied the interactions of baseline cognitive function and effects of different cognitively challenging conditions on landing mechanics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate brain networks have been identified that process information specific to visual attention, cognition, and motor functions in a somewhat independent manner, but the respective processes are integrated within specific areas of the thalamus and basal ganglia (Greene et al, 2020). Although sensory perception, cognitive decision-making, and motor execution are often viewed as distinct processes, references to perceptual-cognitive function (Wang et al, 2017;Hadlow et al, 2018;Wilke et al, 2020;Cardoso Fd et al, 2021) and cognitive-motor function (Brown et al, 2015;Hurtubise et al, 2016;Leone et al, 2017) reflect the high degree of interrelated neural processing that is necessary for successful performance of goal-directed actions. Perception involves awareness of sensory inputs and their inferred causes (Adams et al, 2013), and motor activation occurs before a decision-making process has been completed (Selen et al, 2012;Gallivan, 2014).…”
Section: Assessment Of Perceptual-motor Efficiencymentioning
confidence: 99%
“…Training activities designed to optimize the functional capabilities of athletes have traditionally focused on the improvement of physical attributes, such as muscle strength, power, endurance, and flexibility [8,9]. Few studies have assessed the potential benefit of "cognitive training" for performance enhancement or injury prevention [10][11][12]. Despite compelling evidence of the importance of brain processing efficiency for the generation of rapid, accurate, and consistent motor responses [8,[12][13][14][15], the best means to assess and train cognitive aspects of sport performance remains unclear [16].…”
Section: Introductionmentioning
confidence: 99%